On a fractional q-differential inclusion on a time scale via endpoints and numerical calculations - Mohammad Esmael Samei; Shahram Rezapour (Advances in Difference Equations, 2020)
Abstract By using an endpoint result for set-valued maps, we study the existence of solutions for a fractional q-differential inclusion with sum and integral boundary value conditions on the time scale T t 0 = { t 0 q , t 0 q 2 , … } ∪ { 0 } $\mathbb{T}_{t_{0}}= \{t_{0} q, t_{0} q^{2},… \} \cup \{0\}$ , where t 0 $t_{0}$ is a real number and q ∈ ( 0 , 1 ) $q \in (0,1)$ . We provide an example involving some graphs and algorithms via numerical calculations to illustrate our main result.